2019
DOI: 10.11648/j.ejpm.20190702.13
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Intending Practice on Breastfeeding Among Clinical Medical Students in Bingham University Teaching Hospital, Jos

Abstract: Background: Breastfeeding is a basic human activity, vital to infant and maternal health. A good breastfeeding advice from health professionals can influence a mother's decision to initiate and maintain breastfeeding positively. This study is aimed at assessing clinical medical students' knowledge, attitudes and intending practice towards breastfeeding. Method: Consecutive sampling method was used. Results: Knowledge on the definition of the term EBF was correct in 120 (69.4%) of the students, 47 (27.2%) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
6
3
Order By: Relevance
“…Intention is an important antecedent of behavior [25], and surprisingly, the intention to breastfeed by participants in this study is abysmally poor at 34% when compared with reports from the study by Shehu and Shehu in Jos [19] who reported intention to breastfeed of about 66% among clinical medical students. The study by Padmanabhan et al [23] in India showed as high 98.4% of the participants responding a rmatively, the study by Hamade et al [25] among Syrian and Lebanese female undergraduate university students reported 76.4% and 88.9% respondents respectively con rming their intention to breastfeed their babies.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Intention is an important antecedent of behavior [25], and surprisingly, the intention to breastfeed by participants in this study is abysmally poor at 34% when compared with reports from the study by Shehu and Shehu in Jos [19] who reported intention to breastfeed of about 66% among clinical medical students. The study by Padmanabhan et al [23] in India showed as high 98.4% of the participants responding a rmatively, the study by Hamade et al [25] among Syrian and Lebanese female undergraduate university students reported 76.4% and 88.9% respondents respectively con rming their intention to breastfeed their babies.…”
Section: Discussioncontrasting
confidence: 72%
“…Among the women of reproductive age groups, reliable information about breastfeeding are often times rst heard during pregnancy during antenatal care provided that the lady registers for antenatal care and by which time many of them could have been wrongly informed and wrong opinions about breastfeeding already formed which might be di cult to change. The ndings of this study are not different from that of Shehu and Shehu in Jos [19] among clinical medical students, Padmanabhan et al [23] among female college students in India and Anjun et al [24] among medical students in Pakistan.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Maryam Shehu et al14 Present study shows that 85% of medical interns and 30% of nursing staffs were aware of nutritive benefits of colostrum. Study done by Sanjay Kumar Bhasin et al, showed that almost 92.7% of community health workers had knowledge about the nutritive benefits of colostrum 15.…”
mentioning
confidence: 67%